Reinventing Government:An Analytical Study of Saudi Arabia’s Experience In the Light of Vision 2030 - Alhajj, Abdulmalek (The Arab Journal of Administration, 2020)
This study aims to identify the compatibility of the Saudi government's efforts, according to its national vision (2030) with the concept of Re-inventing government in its different dimensions and characteristics. The analytical, descriptive approach has been used to collect documents and data about the administrative reform such as the policies, programs, initiatives and practices issued by the government. The study reached several conclusions: The Saudi government is making great effort to achieve the widest movement of government reform that is largely in line with the standards and characteristics of the concept of Re-inventing government and the entrepreneurial government. That in terms of the following: mission driven government because it has a clear mission embedded in Vision (2030). In addition, it is the catalytic government by supporting and motivating the private sector, privatization, partnership and creating the investment environment. And to become result oriented government through adopting systems for the performance management and the institutional performance of government agencies. Moreover, to be a revenue government by maximizing and diversifying public revenues, and impose new taxes and fees on services in the sectors of education, health, electricity and expatriate labor. In addition, to become a government managed by adopting the methods of private sector in the public sector. And to become an enterprising government through establishing and financing a number of strategic projects. Furthermore, it seeks to become a decentralized government via delegating administrative levels. As well as being an anticipatory government in dealing with problems and crises through establishing a number of specialized centers. And to be a customer driven government in order to provide a good service to citizens and residents through several means and applications adopted by government agencies. In addition, to be a competitive government to compete itself and the private sector to provide public services. The study also found some similarities between the Saudi experience and the American experience in re-inventing government in terms of Foundations, objectives and tools.